Virtual Sufi Da'wah in Preserving Religious Harmony in North Sumatra - Mawardi Siregar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This article discusses the virtual fragmentation of da'wah by Sufis in preserving religious harmony among the people of North Sumatra. Data were collected from observations, interviews, and documentation. The data is then described in depth using Miles and Huberman's interactive analysis model. The study suggests that Sufi Live is a virtual da'wah fragmentation of the harmony of the Sufi; Tuan Guru Batak (TGB) Ahmad Sabban Rajagukguk to revitalize two da'wah functions, namely the function of the treatise and grace. The role of the treatise is to direct social change in a civilized direction, and the role of grace is to establish religious harmony in North Sumatra. Da'wah themes of tolerance and harmony were delivered in polite language. Sufi Live Facebook delivers fragmented da'wah of religious harmony as a result of the assimilation of academic knowledge, Sufi life stories, and other social experiences that characterize TGB's life.